Alignment study of an electronic distance measuring instruments calibration baseline using geodetic techniques - RAMOS JÚNIOR, Isaac (2024)
This dissertation studied the alignment of the calibration baseline of electronic distance measuring instruments, at Recife campus of the Federal University of Pernambuco. The seven pillars of the calibration baseline, which have a forced centering device, were labeled P1 through P7. Data collection was carried out in two stages. In the first of them, pillars P1 and P7 were used as ends of a presumed alignment, with the other pillars positioned between them, so that if they were all aligned, they would belong to this alignment. Thus, measurements were made using a Topcon GT-605 robotic total station, with P1 and P7 as stations, and through the radiation method, the other pillars were targeted. The field data was transferred to a computer and processed using an original program made in Python. Precision estimates were made for the results, revealing small alignment discrepancies between the pillars. However, pillars P2, P4, P5, and P6 presented values beyond the linear precision of the equipment, which is +/-(2mm +2ppm × D). Due to the geometry found, a closed traverse was perceived between the pillars, with the sequence P1, P3, P4, P7, P6, P5, P2, P1. For this reason, in the second stage, with the same equipment, measurements were taken of three different traverses, using three types of reflective surfaces (360° prism, circular prism, and reflective sheet). The field data were analyzed and subjected to two preliminary statistical tests (Shapiro-Wilk and t-test), followed by adjustment computations for the traverses using the Method of Least Squares, carried out with the AstGeoTop software. After adjustment, distances, angles and coordinates were compared using the 360° prism as reference, and no significant discrepancies were found. Finally, the reference adjusted coordinates of the pillars were used to calculate the distances between them, so they could be compared with previous work. The largest difference found was -2.2 mm, however, it is within the expected linear precision for the distances involved. For future work, it is recommended to carry out high-precision geometric leveling of the baseline to study the vertical component.